China’s foreign investments in the metal sector - Lapi, Thomas; Le Bihan, Joseph; Halloy, José; Issehnane, Sabina; Vidal, Florian (Mineral economics : raw materials report, 2025)
Minerals and metals are crucial to modern technologies. Over the past decades, China has built up a dominant position on the value chain of energy and digital technologies through domestic mining, refining and manufacturing. Chinese foreign direct investments (FDI) in the metal sector are integral to this strategy: by establishing a global value chain system, the expansion of Chinese firms abroad contributes to securing the supply of raw materials for domestic industries. This paper assesses global Chinese FDI in the metal sector from 2005 to 2024 and discusses their integration into China’s global political strategy. Using quantitative and qualitative analysis, we show that China's investments reflect an integrated supply security approach, with interlinked investments in metals, energy and transport infrastructures, exemplified with a case study in Peru. We identified a sharp decline of Chinese FDI in the Australian metal sector over the period studied, reflecting geopolitical tensions and the tightening relationship between Australia and the United States. Chinese firms preferentially target countries with high-market concentration of specific strategic materials such as Indonesia, the Democratic Republic of Congo and Peru, to control extraterritorial mineral reserves. Overall, this mining diplomacy enables China to secure the supply of its industrial sector and strengthen its dominant position in the value chains of strategic technologies.